FACILITY: feeding the family—the intergenerational approach to fight obesity, a cross-sectional study protocol - Vincenti, Alessandra; Calcaterra, Valeria; Santero, Sara; Viroli, Giulia; Di Napoli, Ilaria; Biino, Ginevra; Daconto, Luca; Cusumano, Mariaclaudia; Zuccotti, Gianvincenzo; Cena, Hellas (Frontiers in Pediatrics, 2025)
IntroductionPaediatric obesity has been described by the World Health Organization as one of the most serious health challenges of the 21st century. Over the past four decades, the number of children and adolescents with obesity has increased between 10 and 12-fold worldwide.MethodsChildhood obesity is a complex and multifactorial outcome which can be attributed to factors such as socioeconomic status, ethnicity, lifestyle and eating habits. Beside personal-children-related factors, maternal (education, food knowledge, income) and environmental ones (food environment's features and accessibility) have been proven but their influences are still worth discussion. The cross-sectional study of the “FACILITY: feeding the family—the intergenerational approach to fight obesity” project aims at estimating children prevalence of overweight and obesity and assessing the impacts of lifestyle and of socio-economic-cultural and environmental factors on overweight and obesity.ResultsDue to the current importance of developing multidisciplinary mother-child centred prevention programs, FACILITY cross-sectional study will investigate maternal and child socio-cultural, economic, environmental, health and lifestyle-related risk factors for the development of obesity.DiscussionThe knowledge gained will provide the basis to develop a “primordial prevention program” to early tackle childhood obesity. Clinical Trial RegistrationClinicalTrials.gov, identifier (NCT06179381).